WASTE REDUCTION STRATEGIES IN INDUSTRIAL KITCHENS: A SYSTEMS APPROACH TO SUSTAINABILITY - Novais da Silva , Fernando; Zimmermann, Guilherme; Prim, Pâmela; Amaral Reinert, Kamili (Revista Gênero e Interdisciplinaridade, 2025)
Food waste is a complex global problem, with approximately one-third of the world's food production lost or wasted annually, equivalent to about 1.3 billion tons. This scenario entails serious environmental impacts, such as contributing to greenhouse gas emissions, and social impacts, exacerbating food insecurity. In industrial kitchens and Food and Nutrition Units (FNUs), the transformation of raw materials generates significant amounts of organic waste, becoming a critical focus for sustainable interventions. This article aims to analyze and propose strategies for reducing waste in industrial kitchens, integrating the Circular Economy (CE) as a fundamental pillar for sustainability. Specific objectives include exploring the composting of organic waste, the full utilization of food, and the adoption of ESG (Environmental, Social, and Governance) principles to align practices with SDG 12.3 of the 2030 Agenda, which aims for a global reduction in per capita food waste. The methodology employs a systemic approach to waste transformation, as recommended by the FAO. This involves using frameworks such as the Food Recovery Hierarchy (FHR) to prioritize the destination of these wastes, from source reduction to industrial use and composting. The main results and contributions of this work demonstrate that the implementation of these strategies promotes multifaceted benefits economically, socially, and environmentally. Examples such as Organa Biotech, which uses composting of organic waste, demonstrate the viability and value of such initiatives. The application of these strategies, as observed in case studies and in the Waste Destination Hierarchy (WDH) methodology, shows progress towards more sustainable and circular practices in food management. This work was carried out with the support of the Foundation for Research and Innovation of the State of Santa Catarina (FAPESC), through Call for Proposals No. 50/2024 – Impulsiona SC Program.